Enemy Construction in the Declaration of War against Japanese Empire: CDA Perspective - Asmaradhani, Ahmad Idris (NOBEL: Journal of Literature and Language Teaching, 2019)
This paper seeks to identify and describe the linguistic priming work that President Roosevelt employed in overcoming isolationism in the United States. In his Declaration of War against the Japanese Empire, President Roosevelt asked the American people to trust him with the American forces and American determination using the strategy of enemy construction. Making courageous statements packed in political discourse, he framed the people’s minds into a state of patriotic country defenders and that the Japanese Empire was an enemy and a real danger to the life of the country. His statements are a formulation that America is ready for war with an assurance of a near-absolute victory. Applying the method and theories of Critical Discourse Analysis centered around the framework of "ideological square" and "socio-cognitive approach" for building in-group and out-group as one major aspect of CDA supported with other linguistic theories, this paper aimed at analyzing and describing such linguistic priming to get out of the country isolationist slumber. Based on the results of the analysis and discussion, it is argued that in terms of CDA and socio-cognitive as well as other linguistic theories the enemy construction was inter-textually successful in winning the American people’s consent.